Dilema Efisiensi Pelayanan dan Keamanan Nasional: Analisis Kerentanan Autogate terhadap Deteksi Dini Pelanggaran dan Tindak Pidana Keimigrasian di Tempat Pemeriksaan Imigrasi - Anang Roisul Syafiq; Cantika Rida Augita; Elsa Pasiga Putri (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
The digital transformation of immigration services in Indonesia is marked by the implementation of Autogate technology as an effort to modernize border inspections at various strategic Immigration Checkpoints (TPI). However, the efficiency offered by this automation triggers a dilemma between service speed and the sharpness of national security oversight. This study aims to analyze the vulnerability of the Autogate system toward the early detection of immigration violations and its effectiveness in replacing the human profiling function. Using a qualitative research method with a normative-juridical approach, secondary data were analyzed descriptively-analytically through content analysis techniques. The results show that: (1) Autogate is effective for technical-administrative biometric verification but has not been able to replace the intuitive dimension of human profiling in detecting behavioral anomalies; (2) There are vulnerability points in the sensitivity of biometric sensors, latency in synchronization of prevention and deterrence data (cekal), and potential impersonation modes due to the system's similarity threshold; (3) Operational constraints such as system failures (down system) and limited physical verification without human interaction reduce the ability of Immigration Officers to take immediate action against indications of transnational crimes. This study concludes that ideal border security requires a hybrid oversight model that integrates machine efficiency with the sharpness of human intelligence analysis to maintain border sovereignty towards Indonesia Emas 2045.